Analysis of Financial Performance Based on Environmental Performance and Leverage (In Manufacturing Companies Listed on The Indonesia Stock Exchange in 2010-2013) - Liswatin Liswatin (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This study examines and analyses the role of Corporate Social Responsibility (CSR) as an intervening variable in mediating the effect of leverage and Environmental Performance on Financial Performance. In this study, 56 companies went public and comprised several industries listed in Indonesia Stock Exchange 2010-2013, using a purposive sampling technique. Testing is done using multiple regression analysis (multiple linear regression) with the application of SPSS version 20. The data analysis showed that the leverage and Corporate Social Responsibility (CSR) simultaneously significantly affect financial Performance. It partially influences and is especially effective on the environmental Performance of Corporate Social Responsibility (CSR), while Environmental Performance does not affect the financial Performance. Variable Corporate Social Responsibility (CSR) can become an intervening variable in mediating the effect of leverage on Financial Performance. However, Corporate Social Responsibility (CSR) could not become an intervening variable in mediating the impact of Environmental Performance on Financial Performance.